Peranan literasi digital untuk menangkal pengaruh negatif teknologi bagi mahasiswa di Kota Madiun: The role of digital literacy in counteracting the negative influence of technology on higher education students in Madiun City - Priambodo, Anung; Kristiyandaru, Advendi; Ranu, Meylia Elizabeth; Lisnani, Lisnani; Abadi, Narotama Tegar; Primahani, Grace Navilina (Fakultas Peternakan Universitas Papua, 2025)
ABSTRACT Digital technology has become an integral part of society's life, including students in Madiun City. The rapid development of the digital world provides easy access to information, but it also brings negative impacts, such as social media addiction, hoax spreading, and reduced ability to interact directly, so it is necessary to provide digital literacy training programs that aim to help students develop skills in using technology wisely and critically. Although several programs related to digital literacy have been conducted, many students still do not fully understand how to utilize technology effectively, so the negative impacts can be minimized. The purpose of this community service is to provide digital literacy training to counteract the negative influence of technology on students in Madiun City. The method of implementing this activity includes four stages: preparation, subject and location selection, implementation, and evaluation and analysis. All the data needed during this activity were collected using pretest sheets, posttest sheets, and satisfaction questionnaires. This PKM activity involved 45 people, consisting of 32 participants, 8 partner representatives, and 5 community service team members. The result of this community service activity is a positive response from all participants related to the implementation of the activity, with an average percentage above 85% and participants' understanding of digital literacy and its impact on technology, with an average percentage above 90%. This activity concludes that the activity is interesting, participants feel the benefits of the activity, and participants expect there to be more activities like this. Keywords: Community service; digital literacy; higher education student; Madiun City; Technology. ABSTRAK Teknologi digital telah menjadi bagian integral dalam kehidupan masyarakat, tak terkecuali bagi mahasiswa di Kota Madiun. Perkembangan pesat dunia digital memberikan kemudahan akses informasi, namun juga membawa dampak negatif, seperti kecanduan media sosial, penyebaran hoaks, serta berkurangnya kemampuan berinteraksi langsung sehingga perlu diberikan program pelatihan literasi digital yang bertujuan untuk membantu mahasiswa mengembangkan keterampilan dalam menggunakan teknologi dengan bijak dan kritis. Meskipun beberapa program terkait literasi digital telah dilakukan, masih banyak mahasiswa yang belum sepenuhnya memahami cara memanfaatkan teknologi dengan efektif, sehingga dampak negatifnya dapat diminimalisir. Tujuan pengabdian ini adalah untuk memberikan pelatihan literasi digital untuk menangkal pengaruh negatif teknologi bagi mahasiswa di Kota Madiun. Metode pelaksanaan kegiatan meliputi empat tahap kegiatan yaitu tahap persiapan, tahap pemilihan subjek dan lokasi, tahap pelaksanaan, dan tahap evaluasi dan analisis. Keseluruhan data yang dibutuhkan selama proses kegiatan ini dikumpulkan dengan menggunakan lembar pretest, lembar posttes, dan angket kepuasan terhadap pelaksanaan kegiatan. Kegiatan PKM ini melibatkan 45 orang yang terdiri 32 orang peserta, 8 orang pihak mitra, dan 5 orang tim pengabdian. Hasil dari kegiatan pengabdian ini adalah respon positif dari seluruh peserta terkait pelaksanaan kegiatan dengan persentase rata-rata diatas 85% dan pemahaman peserta terkait literasi digital dan dampaknya terhadap teknologi dengan persentase rata-rata diatas 90%. Kesimpulan dari kegiatan ini adalah kegiatan yang dilakukan menarik, peserta merasakan manfaat dari kegiatan ini, dan peserta mengharapkan akan ada kegiatan seperti ini. Kata kunci: Kota Madiun; Literasi digital; Mahasiswa; Pengabdian kepada Masyarakat; Teknologi.